Alexander Spotswood correspondence - Spotswood, Alexander, approximately 1746-1818.
ALS (1775 December 19) written by Spotswood to Dudley Digges, William Fitzhugh, Joseph Jones, Mann Page, and other members of the Virginia Convention in which Spotswood volunteers to raise a Virginia regiment for service in the Revolutionary War.
Continental Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Digges, Dudley, -- active 1780 -- Correspondence; Fitzhugh, William, -- 1741-1809 -- Correspondence; Jones, Joseph, -- 1727-1805 -- Correspondence; Page, Mann, -- 1749-1781 -- Correspondence; United States. -- Continental Army; Virginia. -- Convention -- (1775-1776); Army officers